Characterization of a Small Supernumerary Marker Chromosome Derived from Xq28 and 14q11.2 Detected Prenatally. (7th May 2018) - Hasegawa, Akihiro; Samura, Osamu; Sato, Taisuke; Matsuoka, Tomona; Ito, Yuki; Kajiwara, Kazuhiro; Aoki, Hiroaki; Inage, Yuka; Kobayashi, Masahisa; Okamoto, Aikou
Abstract : We present the characterization of a case with a small supernumerary marker chromosome (sSMC) detected prenatally derived from Xq28 and 14q11.2 maternal translocation. A 33-year-old Japanese woman, primigravida, underwent amniocentesis because of fetal growth restriction and fetal structural abnormality at 30 weeks of gestation. The fetal karyotype was identified as 47, XY, +mar. Additionally, the single nucleotide polymorphism array analysis revealed copy number gains at Xq28 and 14q11.2. A male infant, weighing 1, 391 g, was delivered at term by cesarean section. Maternal and paternal karyotypes were 46, X, t(X; 14)(q28; q11) and 46, XY, respectively. These findings indicated that the sSMC might have originated from chromosome disjunction at a ratio of three to one. Here we describe a case with an sSMC derived from Xq28 and 14q11.2. Our findings suggest that this sSMC is most likely pathogenic. The collection of additional cases may be required.